Some Results on Semi-preopen Sets - Majeed, R. N.; Nasir, A. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The definition of semi-preopen sets were first introduced by "Andrijevic" as were is defined by :Let (X , ï´ ) be a topological space, and let  A âŠ†,    then A is called semi-preopen set if âŠ†âˆ˜ .        In this paper, we study the properties of semi-preopen sets but by another  definition which is equivalent to the first definition and we also study the relationships among it and (open, Î±-open, preopen and semi-p-open )sets.